Гетероструктурали қуёш батареяси фотоэлементининг фойдали иш коэффициенти (SCIENCE and SOCIETY, 2021)
Solar energy devices convert sunlight into a high-temperature heat energy source of the energy carrier using various shaped mirrors. The heat is transferred to a steam turbine and converted into electricity using a turbogenerator. In this study, the efficiency of a heterostructural solar cell photocell was calculated.